Multicentric Hyaline-Vascular Castleman Disease: A Case Report - Das, Aparna; Tarannum, Sanjana; Kona, Tahera; Saha, Santanu Kumar; Kahhar, MA (Journal of Medicine, 2015)
Castleman disease is a rare lymphoproliferative disorder. Contrary to its closest differential of lymphoma, the disease tends to run a benign course. However the multicentric variety, which is usually of the plasma cell type, has a more sinister prognosis. It is commonly associated with HIV infection. We report a case of a 65 year old man presenting with recurrent episodes of swelling of the whole body and diarrhoea for 3 years. Physical examination revealed generalized lymphadenopathy with hepato-splenomegaly and ascites. Lymph node biopsy revealed histopathological changes consistent with hyaline-vascular type of Castleman disease (multicentric). He was HIV negative. Patient was treated with high dose corticosteroids and discharged with follow up advice. DOI: http://dx.doi.org/10.3329/jom.v16i1.22402 J MEDICINE 2015; 16 : 48-50